Pressupostos da prática educativa na Diocese de Caxias do Sul : 1934 a 1952 - Grazziotin, Roque Maria Bocchese (My University, 2014)
The study tries to analyze the assumptions that fundament the Project for Catholic Restoration of the Diocese of Caxias do Sul, in the period from 1934 to 1952. The data about guidelines and Christian and philosophical principles followed by pioneer confessional schools in the city of Caxias do Sul were collected at the archives of the following institutions: Colégio São José, Escola Nossa Senhora do Carmo and Seminário Nossa Senhora Aparecida. Data were also collected from the archives of Círculo Operário Caxiense, an institution that, through informal education, tried to provide some courses to workers. The basis for these assumptions, which are explicit in this research for the Master´s in Education at the University of Caxias do Sul, in the research line for Education History and Philosophy, go farther back to the Council of Trent, which unified the doctrine, discipline and practice of the Catholic Church. The end of the regime of Ecclesiastical Patronage in Brazil, along with the arrival of immigrant and religious congregations to the country in the end of the XIX century, allowed this Project to consolidate in the state of Rio Grande do Sul. The mechanisms adopted by these institutions favored the collaborative coexistence with the lay State and helped spread the importance of harmonious relations between capital and work to reach development and fight communism. The conclusions reached by this study show that the construction of the educational proposal developed by the religious institutions, based on teaching quality, school environment and discipline, supplementary educational activities, and participation in social and religious activities contributed, on the one hand, for the political, social and cultural development of the city of Caxias do Sul and other cities and towns in the surrounding region known as Serra Gaúcha; and, on the other hand, contributed for the development of a communitarian, humane and fraternal spirit, which are peculiarities of Catholicism, and noticed in the populations in these regions.
O estudo procura fazer uma análise dos pressupostos que fundamentam o Projeto de Restauração Católica na Diocese de Caxias do Sul, no período de 1934 a 1952. Os dados sobre as linhas norteadoras e os princípios cristãos e filosóficos, seguidos pelos colégios confessionais pioneiros em Caxias do Sul, foram levantados junto aos arquivos das instituições: Colégio São José, Escola Nossa Senhora do Carmo e Seminário Nossa Senhora Aparecida, e também consulta aos arquivos do Círculo Operário Caxiense, instituição que procurou, por meio da educação informal, ministrar cursos aos trabalhadores. As bases desses pressupostos, que vêm explícitos nesta pesquisa do mestrado em Educação da Universidade de Caxias do Sul, na linha de História e Filosofia da Educação, remontam ao Concílio de Trento, que unificou a doutrina, a disciplina e a prática da Igreja Católica. O fim do regime do Padroado no Brasil, mais a vinda de imigrantes e de congregações religiosas européias para o Brasil, no fim do século XIX, permitiram que esse Projeto se consolidasse no Rio Grande do Sul. Os mecanismos adotados por essas instituições favoreceram a coexistência colaborativa com o Estado laico e difundiram a importância de relações harmoniosas entre capital e trabalho para alcançar o desenvolvimento e combater o comunismo. As conclusões a que este estudo chegou é que a construção da proposta educativa desenvolvida pelas instituições religiosas, baseada na qualidade de ensino, no ambiente e disciplina escolar, nas atividades educativas complementares e na participação em atividades religiosas e sociais, contribuiu, de um lado, para o desenvolvimento político, social e cultural do município de Caxias do Sul e dos municípios da região da Serra Gaúcha; e, de outro lado, para o desenvolvimento do espírito comunitário, humano e fraterno, próprios do catolicismo, marcados nas populações dessas regiões.
Keywords: Educação; Colégios confessionais; Escolas católicas; Educação religiosa; Atividades educativas, sociais e políticas; Instituições religiosas; Igreja e educação - Caxias do Sul (RS); Escolas católicas - Caxias do Sul (RS); Ensino religioso; Confessional schools; Catholic schools; Religious education; Political, social and educational activities; Religious Institutions; Church and education - Caxias do Sul (RS) (Brazil); Catolic schools - Caxias do Sul (RS) (Brazil); Religious education